Experimental Algorithms 11th International Symposium, SEA 2012, Bordeaux, France, June 7-9, 2012. Proceedings - Klasing, Ralf.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 11th International Symposium on Experimental Algorithms, SEA 2012, held Bordeaux, France, in June 2012. The 31 revised full papers presented together with 3 invited papers were carefully reviewed and selected from 64 submissions and present current research in the area of design, analysis, and experimental evaluation and engineering of algorithms, as well as in various aspects of computational optimization and its applications.
Keywords: Computer science; Computer Communication Networks; Computer software; Artificial intelligence; Algorithms; Computer Science; Algorithm Analysis and Problem Complexity; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Computer Communication Networks; Programming Techniques; Algorithms